Peran Teman Sebaya Terhadap Hasil Belajar Peserta Didik Pada Tema 8 Subtema 1 Di Kelas V SD Negeri 01 Percontohan Meulaboh - Rika Melisa; Aida Fitri; Mislinawati Mislinawati (Universitas Syiah Kuala, 2023)
In thematic lessons, many students still have low learning outcomes in Sub-theme 1 (Humans and the Environment) which is in theme 8 (The Environment of Our Friends). This study aims to describe the role of peers in student learning outcomes on theme 8 sub-theme 1 in class V SD Negeri 01 Pilot Meulaboh. The approach used in this research is qualitative, and descriptive type. All of the fifth-grade students were 25 students, as the subject of this study with details of 10 males and 15 females. Data were collected through observation in order to see a picture of what was found in the field, interviews for the data obtained were more accurate and tests were used to obtain student learning outcomes. All data collected which will be processed through the data analysis stage is 1 data reduction, 1 data presentation, and 1 conclusion drawing from all 1 data. Based on the results of the research, it shows that the role of peers on the results of lessons by students has been very helpful in learning activities. Based on observations, interviews and peer test questions play a role in the learning outcomes of students in the classroom, the more interactions with peers related to learning in the classroom that students do not understand, and also support from peers regarding the results of learning activities carried out in groups, the results students' learning will be better, based on the results of the study it is known that by applying Vygotsky's concept of the Zone of Proximal Development when tasks that are too difficult are mastered by students alone but can be learned with the help of peers who are more capable